TEKNIK PENGEMASAN BENIH KAKAO (Theobroma cacao L) DALAM PENYIMPANAN - Nengsih, Yulistiati; Hartawan, Rudi (Universitas Batanghari, 2018)
Cocoa seeds are included in recalcitrant seeds that have the characteristic of aging and regrowth of seeds during storage, viability of seeds decreases when their water content is decreased (12-31%) and can not stand to be stored at low temperature and humidity. For the provision of quality seeds need to be mastered technology seed storage properly. The aim of this research is to get the proper packing technique in maintaining viability of cocoa seed (Theobroma cacao L) during storage. The research will be conducted from Pebruari to Juni 2018, at Batanghari University Basic Laboratory. The design used is the Randomized Complete environment with the treatment of cardboard packaging with several ventilation holes: P0 = cardboard without ventilation, P1 = 2% ventilation box, P2 = 4% ventilation box, P3 = 6% ventilation box and P4 = cardboard box 8 %. The observed variables were: percentage of moisture content, percentage of seeds germinated in storage, percentage of sprout gain after storage, germination rate after storage, percentage of moldy seeds in storage and identification mushrooms. To see the effect, F test was done at 5% level, then continued with Duncan test at α 5%. The result of the research showed that the treatment of the packing ventilation had an effect on the percentage parameter of moldy and germinated seed in storage and seed viability and vigor. In the treatment between ventilation, did not show any difference, but economically recommended the use of ventilation by 8%. Until storage on day 12 of the treatment of packaging vents can withstand the fungus attack 17.19% compared to control. The amount of ventilation does not show ability to withstand viability and vigor after storage. The fungus identified in seed storage is Fusarium spp. and Aspergillus spp Keywords: Recalcitrant, viability, moisture content of seeds AbstrakBenih kakao termasuk benih rekalsitran yang mempunyai sifat mengalami penuaan dan kemunduran benih selama penyimpanan, viabilitas benih menurun apabila diturunkan kadar airnya (12-31%) dan tidak tahan disimpan pada suhu dan kelembaban rendah. Untuk pengadaan benih berkualitas perlu dikuasai teknologi penyimpanan benih secara tepat. Penelitian bertujuan untuk mendapatkan teknik pengemasan yang tepat dalam mempertahankan viabilitas benih kakao (Theobroma cacao. L) selama penyimpanan. Penelitian dilaksanakan pada bulan Pebruari sampai Juni 2018, di Laboratorium Dasar Universitas Batanghari. Rancangan yang digunakan adalah rancangan lingkungan Acak Lengkap dengan perlakuan kemasan kardus dengan beberapa lubang ventilasi yaitu : P0= kardus tanpa ventilasi, P1= kardus ventilasi 2%, P2= kardus ventilasi 4%, P3= kardus ventilasi 6 % dan P4= kardus ventilasi 8%. Peubah yang diamati adalah: Kadar air benih, persentase benih yang berkecambah dalam penyimpanan, persentase daya kecambah setelah penyimpanan, kecepatan berkecambah setelah penyimpanan, persentase benih berjamur dalam penyimpanan dan identifikasi jamur. Untuk melihat pengaruh perlakuan, dilakukan uji F pada taraf 5%, kemudian dilanjutkan dengan uji Duncan pada taraf α 5%. Hasil penelitian menunjukkan bahwa perlakuan ventilasi pengemasan berpengaruh terhadap peubah persentase benih berjamur dan berkecambah dalam penyimpanan serta viabilitas dan vigor benih. Pada perlakuan antar ventilasi, tidak menunjukkan adanya perbedaan, akan tetapi secara ekonomis dianjurkan penggunaan ventilasi sebesar 8%. Sampai penyimpanan pada hari ke-12 perlakuan ventilasi kemasan dapat menahan serangan jamur 17,19% dibandingkan kontrol. Jumlah ventilasi tidak menunjukkan mampu menahan viabilitas dan vigor setelah penyimpanan. Jamur yang teridentifikasi dalam penyimpanan benih adalah Fusarium spp. dan Aspergillus spp. Kata kunci : Rekalsitran, viabilitas, kadar air benih